Integrated predictive call admission control and resource reservation for wireless networks: an adaptive filtering approach. Issue 7 (22nd June 2012) - Ukil, Arijit; Misra, Iti Saha; Bader, Faouzi; Demestricas, Panagiotis; DaSilva, Luiz; Harada, Hiroshi
ABSTRACT Allocation of network resources in determining whether the connection can be established or not while maintaining stringent quality of service under desired traffic condition is the principal objective of a call admission control (CAC) algorithm. Radio resources when applied to real‐time applications may lead to over‐provisioning in wireless networks. Although CAC and resource reservation are treated independently in the literature, an attempt has been undertaken in this paper to formulate an integrated algorithm capable of providing accurate predictive CAC and resource reservation techniques with optimal resource utilization. The algorithm has been developed using the concept of adaptive filtering. The principal focus has been directed to introduce normalized least mean square adaptive filtering to estimate the source traffic characteristics. With extensive simulation results, we show the effectiveness of the proposed scheme and analyse the significance of different parameters involved in the scheme to optimize the overall radio resource management.Copyright © 2012 John Wiley & Sons, Ltd.